SEMIPRESIDENCIALISMO E A LONGEVIDADE DOS GOVERNOS DE COABITAÇÃO: UM ESTUDO DE CASOS DIVERSOS SOBRE BULGÁRIA, ROMÊNIA, FRANÇA E PORTUGAL - Loureiro, Raysa Dantas (2020)
What does characterize cohabitation periods in semi-presidential systems? This is the main purpose of this research. Current political science literature has considered cohabitation a threat to government stability, but we can find cohabitation government